Sea-surface temperature, productivity and hydrological changes in the Northern Indian Ocean (Maldives) during the interval similar to 575-175 ka (MIS 14 to 7) - Alonso-Garcia, Montserrat (2021)
The South Asian Monsoon (SAM) drives seasonal changes in the atmospheric and ocean circulation of the tropical Indian Ocean, affecting precipitation on land and oceanic primary productivity. This work examined sediments from the International Ocean Discover Program (IODP) Site U1467 (IODP Expedition 359) located in the Maldives Inner Sea (Northern Indian Ocean) at a water depth of 487 m. The Maldives Inner Sea is a perfect location to study past changes in tropical climate and ocean circulation related to monsoon dynamics in the Equatorial Indian Ocean. This study focuses on the similar to 575-175 ka interval, from Marine Isotope Stage (MIS) 14 to 7, an important period for human evolution and dispersal to Eurasia. We reconstructed sea-surface temperature (SST), based on alkenone unsaturation index (U-37(K')), hydrological changes, based on terrestrial input of n-alkanes, and past surface ocean productivity, based on total C-37 alkenones concentration. The U-37(K')-SST record shows a difference of about 1.5 degrees C between glacial and interglacial periods, clearly showing all stages and substages from MIS 14 to 7, and revealing a connection between ice sheets extension and SST at the equatorial region. The n-alkanes concentration and average chain length index indicate vegetation changes at the Indian Peninsula with drier conditions generally associated with glacial periods. Precipitation increases abruptly at the end of terminations, lasting for a variable time interval in each interglacial period, except for MIS 13. However, other mechanisms superimposed to the glacial-interglacial forcing, such as the Indian Ocean Dipole (IOD) mode, have been invoked to explain shorter-scale variability in precipitation over India. The total alkenone concentration record indicates that primary productivity at Site U1467 is strongly associated with orbital changes, probably related to the summer inter-tropical insolation gradient (SITIG, 23N-23S on June 21st). High primary productivity occurred during intervals of low SITIG, which resulted in strong inter-monsoon (April-May and October-November) Indian Ocean Equatorial Westerlies (IEW) and reduced precipitation in the equatorial region. This mechanism may also be related to the IOD, which affects the strength of the IEW.